“Beyond Morality.” Discourse on Homosexuality in Croatian Newspapers from the Sociosemiotic Perspective: Comparison of Two Periods - Antulov, Sandra; Bertoša, Mislava (2011)
Sociosemiotics is, among other issues, focused on the modes in which different social discourses construct, legitimate, recognize or attack systems of values and beliefs, as well as relations of power and domination in the society. It aims to examine their ideological effects, hegemonic processes, and to point out their discursive and semiotic nature. Sociosemiotic perspective emphasizes the importance of meanings and values as necessary for the effectiveness of ideological processes and actions: this implies the impacts of the social discourses in spreading, circulating, cultivating and subverting these ideas and values. In this paper we focus on two examples that show how such social discourses in their historic specificity affect the establishing and acceptance of heteronormative meanings and values. We aim to analyse heteronormativity as a discursive principle which organises sexuality in general, including the gay population who is part of its paradigm. In the context of social and historical processes, it changes its discursive strategies, utterance aspects and visual representations, retaining, however, its hegemonic position and normative character. Focusing on ideas and perspectives developed in the field of Greimasian French and Italian sociosemiotics, this paper aims to analyse and to compare two Croatian newspaper articles on the gay population in Croatia dating from two different periods: one from 1992 and the other from 2008. Sociosemiotic analysis integrates both verbal and visual elements of the two articles, and it explores the differences in the discursive strategies of the construction and representation of homosexuality, analyses the differences in aspects of utterances and utterance actors involved, as well as tries to examine how particular meanings are used for the critique or support of the dominant system of beliefs and values. This analysis shows that these concrete representations of homosexuality transform their discursive strategies moving towards empowering and more decisive types of discourses, but that in their deep (semiotic) level still remain in the setting of the dominant heteronormative paradigm.
Projekt MZOS
ENG